Water always wins : thriving in an age of drought and deluge - Gies, Erica (The University of Chicago Press, 2022)
"Water Always Wins transports us around the world and back through time, exposing us to better ways to live with water. Gies introduces us to water experts the world over as they search for clues to water's past and present, using close observation, historical research, ancient animal and human wisdom, and cutting-edge science to effect change. We become more aware of the ways in which modern civilizations speed water away, erasing its slow phases on the land. But that's when, Gies says, "the magic happens": the slow phases absorb floods, store water for droughts, and feed natural systems. Innovators in what she calls the Slow Water movement are accommodating that desire, and showing us how to forge a more resilient future"--